Affordable, accessible, healthy: Urban consumer knowledge and the use of indigenous food - Vilakazi, Nokuthula (New Agenda: SA Journal of Social and Economic Policy, 2024)
For many residents in peri-urban areas, the price of essential healthy food items in supermarkets is unaffordable. At the same time, the more affordable informal markets tend to offer highly processed foods with low nutritional value. Indigenous foods are recognised for their potential to improve food and nutrition security, reduce malnutrition and enhance health and well-being, yet their use in urban areas is limited. In this article NOKUTHULA VILAKAZI explores the gap in urban consumers’ knowledge about the availability, production, preparation and use of indigenous foods in the City of Durban, eThekwini Municipality, with a specific focus on cowpeas.